PENGARUH KESELAMATAN DAN KESEHATAN KERJA (K3) DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA UNIT PELAYANAN GANGGUAN PT. PLN (PERSERO) ULP BATURAJA: influence of Occupational Safety and Health (OSH) on employees’ work productivity at the PT. PLN (PERSERO) ULP Baturaja Service Unit for Disturbances (Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2023)
The data analysis technique used was Multiple Linear Regression. Based on the partial analysis, there was an influence of Occupational Safety and Health (OSH) on employees’ work productivity at the PT. PLN (PERSERO) ULP Baturaja Service Unit for Disturbances with a t-value of 2.900. The Work Discipline variable partially had an influence on employees’ work productivity at the PT. PLN (PERSERO) ULP Baturaja Service Unit for Disturbances with a tvalue of 3.729. Simultaneously, it was found that there was an influence of Occupational Safety and Health (OSH) and Work Discipline on employees’ work productivity at the PT. PLN (PERSERO) ULP Baturaja Service Unit for Disturbances. The determination coefficient (R2) obtained was 0.854. This means that the contribution of the influence of Occupational Safety and Health (OSH) and Work Discipline on work productivity was 85.4%, while the remaining 14.6% was influenced by other variables outside of this research such as wages, loyalty, and work ethic (Afandi, 2018: 93)